2005
DOI: 10.1021/jp053536l
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Initial Degradation Steps of Four Major Dye Chromophores:  Study of Their One-Electron Oxidation and Reduction by EPR, ENDOR, Cyclic Voltammetry, and Theoretical Calculations

Abstract: The degradation of dyes is frequently initiated by one-electron oxidation or reduction; however, relatively little is known about the initially formed radicals. Acid Green 25 (AG25), Crystal Violet (CVI), Methylene Blue (MB), and Acid Orange 7 (AO7), representing paradigms of four types of commercial organic dyes, were therefore investigated in terms of their redox behavior. Their redox potentials in MeCN and buffered aqueous solutions were determined by cyclic voltammetry. The structures of the one-electron r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…9 for 1 + Cl À /DMF/KOH). The spectrum was simulated using hyperfine parameters similar to those reported by Stanoeva [38], where a similar ESR spectrum was obtained for 1 + Cl À reduction with potassium in dimethoxyethane solvent.…”
Section: 131mentioning
confidence: 93%
“…9 for 1 + Cl À /DMF/KOH). The spectrum was simulated using hyperfine parameters similar to those reported by Stanoeva [38], where a similar ESR spectrum was obtained for 1 + Cl À reduction with potassium in dimethoxyethane solvent.…”
Section: 131mentioning
confidence: 93%
“…ultramarine (Arieli et al 2004;Goslar et al 2009) and crystal violet (Brezova et al 2004;Stanoeva et al 2005). EPR provides detailed information not only on the chromophore itself, but also on its surroundings, in the form of the vehicles around the paramagnetic ion.…”
Section: Reference Samples Of Copper Dyesmentioning
confidence: 99%
“…It was reported that the hydrazone form should be favorable at equilibrium in aqueous medium when the hydroxyl group should be positioned in a naphthol ortho to the azo bond of azo dyes (such as, Orange I). Thus, for Orange II, the intramolecular hydrogen bonding could be formed in the solution [17][18][19]. Different from Orange I and Orange II, Methyl Orange is derived from the p-dimethylaminoaniline group linked with azo bond.…”
Section: Discussion On the Effect Of Substituent Groupsmentioning
confidence: 99%
“…Consequently, the N N cleavage of Orange I and Orange II may be comparatively easier than that of Methyl Orange. Based on the previous literatures [3][4][5]12,19,20], the suggested degradation pathways of Orange I, Orange II and Methyl Orange through the cleavage of the azo bond by the reductive processes are shown in Fig. 6.…”
Section: Discussion On the Effect Of Substituent Groupsmentioning
confidence: 99%